Macroprocess 06 Auditing - Organizational Design Division (Inter-American Institute for Cooperation on Agriculture, 2020)
The Macroprocess 6 Auditing aims to "Verify IICA's compliance with existing regulations, policies and processes, its adequate use of resources and efficient management". Scope: Hemispheric level. Centralization for technical regulatory actions. Execution of validations actions at Headquarters and IICA Delegations, as well as for externally founded projects.